The Intersection of Nanotechnology and Agriculture: Enhancing Soil Fertility and Nutritional Outcomes – A Comprehensive Review - Gulaiya, Shani; Manzoor, Uzma; Singh, Sahadeva; Yadav, Kamalkant; Yadav, Akanksha Singh; Kumar, Ravi; Ahmed, Bulbul; Kumar, Ravindra (Journal of pure & applied microbiology : an international research journal of microbiology, 2025)
A vast global repository of biodiversity, soil is mostly controlled by soil bacteria. “Nanofertilizers,” a novel class of formulations based on nanoparticles, are meant to revolutionize traditional nutrition delivery techniques. Nanoscience has inspired revolutions in peripheral fields through promising methods like nano-pesticides, nano-sensors, nano-magnets, nano-films, nano-filters, and nano-nutrients. This allows for improved input management and conservation, which makes it possible to boost agricultural output. Their main features, like their huge surface area, controlled release mechanisms, and specially designed nutrient encapsulation, provide several advantages for optimizing plant nutrient uptake. Despite the fact that agriculture is a broad subject, the use of nanotechnology in this industry has increased over the past decade due to public interest and the field’s modest rate of expansion. By activating soil enzymes, nanotechnology improves soil fertility and nutrient transfer. Nanomaterials (NMs) and rhizospheric bacteria can work together to enhance soil health and plant growth. Together, nanotechnology applications provide a comprehensive strategy for controlling plant nutrition and health, enabling a reduction in chemical inputs and the harm they do to the environment. Nanosensors can monitor soil and plant health in real-time, allowing for more accurate and efficient crop management. NPs can also improve the delivery of nutrients and pesticides to plants, reducing waste and increasing effectiveness.